Use of accelerometry to measure physical activity in adults and the elderly Actividad física en adultos y ancianos evaluados por acelerometría Actividade física em adultos e idosos avaliados por acelerometria - Teresa Bento; António Cortinhas; José Carlos Leitão; Maria Paula Mota (Universidade de São Paulo, 2012)
OBJECTIVE: To review the use of accelerometry as an objective measure of physical activity in adults and elderly people. METHODS: A systematic review of studies on the use of accelerometty as an objective measure to assess physical activity in adults were examined in PubMed Central, Web of Knowledge, EBSCO and Medline databases from March 29 to April 15, 2010. The following keywords were used: "accelerometry," "accelerometer," "physical activity," "PA," "patterns," "levels," "adults," "older adults," and "elderly," either alone or in combination using "AND" or "OR." The reference lists of the articles retrieved were examined to capture any other potentially relevant article. Of 899 studies initially identified, only 18 were fully reviewed, and their outcome measures abstracted and analyzed. RESULTS: Eleven studies were conducted in North America (United States), five in Europe, one in Africa (Cameroon) and one in Australia. Very few enrolled older people, and only one study reported the season or time of year when data was collected. The articles selected had different methods, analyses, and results, which prevented comparison between studies. CONCLUSIONS: There is a need to standardize study methods for data reporting to allow comparisons of results across studies and monitor changes in populations. These data can help design more adequate strategies for monitoring and promotion of physical activity. OBJETIVO: Analizar el uso de la acelerometría como medida objetiva de actividad física en adultos y ancianos. MÉTODOS: Revisión sistemática en las bases PubMed, Web of Knowledge, EBSCO y Medline, del 29 de marzo al 15 de abril de 2010. Se utilizaron en la búsqueda las palabras-clave: "accelerometry", "accelerometer", "physical activity", "PA", "patterns", "levels", "adults", "older adults" y "elderly", de forma aislada o combinadas usando "and" o "or". Las listas de referencias de los artículos recuperados fueron examinadas para encontrar artículos potenciales. De los 899 estudios localizados, 18 fueron revisados integralmente, y sus datos extraídos y analizados. RESULTADOS: Once estudios se realizaron en los Estados Unidos, cinco en Europa, uno en Camerún y otro en Australia. Pocos involucraron ancianos, y sólo uno se refirió a la estación o período del año en que transcurrió la colecta de datos. Los métodos, análisis y resultados discreparon entre los estudios, imposibilitando un análisis más a fondo. CONCLUSIONES: Se debe promover la estandarización de procedimientos que permitan comparar resultados entre estudios y monitorear alteraciones en una población. Estos datos contribuyen adecuación de las estrategias de monitoreo y promoción de la actividad física. OBJETIVO: Analisar o uso da acelerometria como medida objetiva da atividade física em adultos e idosos. MÉTODOS: Revisão sistemática nas bases PubMed, Web of Knowledge, EBSCO e Medline, de 29 de março a 15 de abril de 2010. As palavras-chave utilizadas na busca foram: "accelerometry", "accelerometer", "physical activity", "PA", "patterns", "levels", "adults", "older adults" e "elderly", isoladamente ou combinadas usando "and" ou "or". As listas de referências dos artigos recuperados foram examinadas para captar artigos potenciais. Dos 899 estudos localizados, 18 foram revistos integralmente, com seus dados extraídos e analisados. RESULTADOS: Onze estudos foram realizados nos Estados Unidos, cinco na Europa, um em Camarões e outro na Austrália. Poucos envolveram idosos, e apenas um referiu a estação ou período do ano em que decorreu a coleta de dados. Os métodos, análises e resultados divergiram entre os estudos, impossibilitando uma análise mais aprofundada. CONCLUSÕES: Deve-se promover a padronização de procedimentos que permitam comparar resultados entre estudos e monitorizar alterações numa população. Esses dados contribuem para a adequação das estratégias de monitoramento e promoção da atividade física.